n-Tuplet Coincidence Point Theorems in Partially Ordered Probabilistic Metric Spaces - Karaaslan, Arife Aysun; Karakaya, Vatan (HINDAWI LTD, 2018)
In this paper, we investigate existence of n-tuplet coincidence point theorems in partially ordered probabilistic metric spaces. Also, we gave uniqueness of n-tuplet fixed point theorems in this space.
Keywords: CONTRACTIONS; Mathematics